Perhitungan Beban Pencemaran Air Sungai Cibabat Kota Cimahi Provinsi Jawa Barat - Mochammad Azhar Rais Alfaroby; Eka Wardhani (Jurnal Serambi Engineering, 2021)
The lack of domestic wastewater management services in the Cibabat River Basin has resulted in the Cibabat River being a place to collect domestic wastewater. This of course can reduce water quality  as well as reduce the function of the river itself.  The Cibabat river is known to be a sub-watershed of the Citarum River with a surface   area of  1,855 km2. Activities in the Cibabat watershed  contribute  to the pollution load that  causes the water quality of the Cibabat River to decline, which of course has an impact on the decrease  in the quality of the river and increase  in the polluting  load that the river will receive. The research method uses the calculation of the pollutant  load based on Permen LH 115/2003. The data used are  secondary data from DLH Cimahi City, which  conducted a water quality analysis at three points during  three different seasons in 2019. One of the steps to overcome and control the pollution that occurs is to determine the actual pollutant load so that it can easily determine the application of effective technology  for controlling river water pollution  in the Cibabat River at theCimahi City.